Application of Nanomaterials and Related Drug Delivery Systems in Autophagy - Mei, Ling; Liao, Kai; Chen, Haiyan; Zhang, Yifan; Zhang, Zihan; Li, Qiangwei; Li, Man (Molecules (Basel, Switzerland), 2024)
Autophagy, a lysosomal self-degradation pathway, plays a critical role in cellular homeostasis by degrading endogenous damaged organelles and protein aggregates into recyclable biological molecules. Additionally, it detoxifies extracellular toxic substances, including drugs and toxic materials, thereby preserving the stability of the intracellular environment. The swift progression of nanotechnology has led to an increased focus on understanding the relationship between nanomaterials and autophagy. The effects of various nanomaterials and nano drug delivery systems on autophagy and their biological functions have been preliminarily assessed, revealing that modulation of intracellular autophagy levels by these agents represents a novel cellular response mechanism. Notably, autophagy regulation based on nanomaterials or nano drug delivery systems for a range of diseases is currently the subject of extensive research. Given the close association between autophagy levels and tumors, the regulation of autophagy has emerged as a highly active area of research in the development of innovative tumor therapies. This review synthesizes the current understanding of the application of nanomaterials or nano drug delivery systems on autophagy and their potential biological functions, suggesting a new avenue for nanomaterial-based autophagy regulation.